Comparison of cheliped weight and growth in two species of crabs of the genus Callinectes (Brachyura, Portunidae) - Guerrero-Ocampo, C. M.; Negreiros-Fransozo, M. L.; Costa, T. M. (Inst Tecnologia Parana, 1998)
A comparison of the cheliped's weight in two species of the genus Callinectes was accomplished. The species C. danae e C. ornatus were collected by two otter trawl in Ubatuba bay (23 degrees 26' S and 45 degrees 02' W). The allometric constants obtained from the regression adjusted to a power function (Y = aX(b)) were analyzed. These species presented different allometry degrees for each sex considered. The relation Pe x PC presented positive allometry for sex of both species, but male presented higher positive allometry than female. C. danae presented higher positive allometry for chelipeds than C. ornatus. We suggest here that C. danae could be indicated to be submitted to grow out in ponds since it reaches higher size and bigger chelipeds.
Keywords: Portunidae; Callinectes; siris; quelipodo; crescimento relativo; swimming crab; cheliped; relative growth